THE INFLUENCE OF SMART CITY ELEMENTS ON SMART CITY DEVELOPMENT STRATEGIES IN MEDAN CITY - Thalita Eka Kharisma; Sirojuzilam; Raina Linda Sari (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of Smart City elements including Smart Governance, Smart Society, Smart Branding, Smart Living, Smart Environment, and Smart Economy on the Smart City concept development strategy in Medan City. Medan City as one of the major cities in Indonesia faces complex urbanization challenges, so the implementation of Smart City is expected to improve the efficiency of public services and the quality of life of the community. The research method uses a quantitative approach with Structural Equation Modeling (SEM) techniques based on Partial Least Squares (PLS) to test the relationship between variables. Primary data were collected through questionnaires distributed to 100 respondents who use Smart City services in Medan. The results show that Smart Governance and Smart Living variables have a positive and significant effect on the Smart City development strategy, while Smart Society, Smart Branding, Smart Environment, and Smart Economy do not have a significant effect. The research model is able to explain 71.9% of the variation in Smart City development strategies in Medan City. This finding indicates that improving governance and the quality of life of citizens are crucial for the success of Smart City development. The recommendation of this study is to strengthen Smart Governance and Smart Living to support innovation and sustainable public services in Medan City.